Benign Anorectal Disorders An Update - Vannelli, Alberto; Cornelia Lazar, Daniela (IntechOpen, 2023)
Hemorrhoids, anal fissures, and fistulas are common benign anorectal diseases that have a significant impact on patients' lives. This book examines state-of-the-art research relating to the etiology, diagnosis, prevention, and treatment of benign anorectal diseases. It emphasizes the importance of a multidisciplinary approach.